Mental Health Problems among Adolescent Prisoners: A Literature Review - Hidayati, Nur Oktavia; Dewi, Syafira; Mentari, Vanessa Zian; Nurhidayah, Ikeu (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: The purpose of this literature review is to identify mental health problems in adolescent prisoners. Methods: A literature review method was used. PubMed, Sage Journal, Springer, and EBSCO were used to search for articles. This literature review's inclusion criteria were English publications published during the last ten years, and qualitative and quantitative study. Results: The results obtained were mental health problems that often appear in adolescent prisoners such as behavioral disorders, hyperactivity, violent behavior, Oppositional Defiant Disorder (disobedient behavior), substance use disorders, and anxiety disorders. Conclusions: Mental health services for adolescents in prisons need to be improved to prevent more serious health problems.